THE INFLUENCE OF FAMILY HARMONY TO SELF ESTEEM STUDENT AT SMA NEGERI 1 SIDAMANIK, SIMALUNGUN DISTRICT, NORTH SUMATRA PROVINSI - Listra Septiana Silalahi; Meisie L. Mangantes; Hans Frans Pontororing (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
Family harmony is an important factor in students' self-esteem. Where the high and low levels of family harmony greatly affect the level of self-esteem of students. This study aims to reveal the influence of family harmony on students' self-esteem at SMA Negeri 1 in Sidamanik. This research uses quantitative research methods. Data collection techniques using a questionnaire/questionnaire. But before collecting data, each item in the questionnaire was tested for its validity and reliability. The population of all students at SMA Negeri 1 in Sidamanik is approximately 863 students. Samples were taken based on the descriptive correlational research design and totaled at least 30 respondents. The analysis technique used is a simple regression technique. Before analyzing the data for hypothesis testing, the requirements for inferential analysis were first tested, namely the normality test and linearity test with the help of the SPSS (statistical package for service solution) 23 computer program for windows. The results of this study stated that family harmony with a positive direction was significant with students' self-esteem. This means that the higher the level of family harmony, the higher the student's self-esteem. Conversely, the lower the level of family harmony, the lower the student's self-esteem. In this study it is suggested to parents to further improve family harmony so that children have high self-esteem.